Politically Optimal Fiscal Policy - Yakadina, Irina (IMF Working Papers; Working Paper ;, 2007)
Why do governments issue large amounts of debt? In what sense and for whom is such a policy optimal? We show that twisting the optimal taxation paradigm produces very reasonable predictions for debt and real interest rates. Adding an extra dimension of uncertainty about the political planning horizon gives rise to a positive and very plausible government debt-to-GDP ratio of about 55 percent in a model that otherwise predicts negative government debt. We quantify the impact of political uncertainty on steady state and business cycle dynamics. We illustrate how populist tax cuts can cause business cycle fluctuations.